Epoxy resin adhesive with visualized bonding process and preparation method thereof

By introducing the fluorescent agent TPE-2MI in epoxy resin adhesives by dynamic covalent chemical crosslinking, the problem of degradation of mechanical properties of traditional adhesives during repeated bonding is solved, and the repetitive bonding of the adhesive and the synchronous changes in fluorescence intensity and bonding strength are achieved, ensuring the balance of mechanical properties and fluorescence properties of the adhesive, and visual monitoring of the bonding process is achieved.

CN116239980BActive Publication Date: 2025-03-04SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310157680.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-03-04
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

Traditional adhesives are difficult to recycle and recycle, and their mechanical properties decrease during repeated bonding, resulting in failure of bonding and affecting daily life and industrial production.

Method used

Dynamic covalent chemical crosslinking is used to introduce the fluorescent agent TPE-2MI into the epoxy resin adhesive, so that the fluorescence intensity changes with the bonding strength during the bonding process, thereby achieving visual monitoring of the bonding process.

Benefits of technology

Repeatable adhesive bonding and synchronous changes in fluorescence intensity and bond strength of the adhesive are achieved, ensuring the balance of mechanical properties and fluorescence properties of the adhesive, and the real-time visual monitoring of the bonding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239980B_ABST
    Figure CN116239980B_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy resin adhesive for bonding process visualization and a preparation method thereof, the adhesive is composed of component A and component B, the component A is a furan-modified linear epoxy polymer (FEP) obtained after the reaction of glycidyl ether monomer and 2-furanmethylamine, and the component B is a mixture of tetraphenylethylene (TPE-2MI) modified by bismaleimide and bismaleimide and compound (x-2MI). The epoxy resin adhesive for bonding process visualization prepared by the present invention has the characteristics of repeatable bonding, fluorescence intensity can change in real time with adhesive bonding strength, can realize visual tracking of adhesive bonding process, and is expected to be applied to the fields of cultural relics restoration, medical treatment, automobile assembly, anti-counterfeiting, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an epoxy resin adhesive with visualized bonding process and a preparation method thereof. Background Art

[0002] Traditional adhesives are usually prepared using various thermosetting cross-linked polymer materials, such as epoxy, acrylate, and polyurethane. However, due to the difficulty in recycling and the inability to recycle, the large-scale use of traditional adhesives will inevitably cause environmental pollution and economic waste. In order to solve the above problems, people have focused on the research of reversible adhesives. This type of adhesive uses dynamic bonds to construct a dynamic polymer network. By using the property of dynamic bonds that can be broken and reorganized under certain conditions, the adhesive can achieve repeated bonding. This type of dynamic chemical reaction includes Diels-Alder (DA) reaction, disulfide exchange reaction, borate exchange reaction, etc.

[0003] However, the recycling of adhesives will also bring some problems. For example, during the repeated bonding process, the mechanical properties of the adhesive will decrease due to environmental factors, which may cause the adhesive to fail, causing huge losses in daily life and even in industrial production, and even endangering people's safety. Fluorescence has broad application prospects in the fields of luminescent sensing, information coding, anti-counterfeiting marking, and biological imaging. Since adhesives are usually colorless and difficult to distinguish under visible light, fluorescent adhesives that can emit fluorescence under ultraviolet light have attracted widespread attention. However, since fluorescent substances are usually introduced into adhesives by doping or covalent chemical bonding, their fluorescence properties are almost unaffected by cross-linking structures and bonding effects. Therefore, developing a preparation technology for epoxy resin adhesives that can combine mechanical properties with fluorescence properties and visualize the bonding process is a fundamental way to solve the current problems in this field. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies in the prior art and to provide an epoxy resin adhesive with a visualized bonding process. Compared with the prior art products, the epoxy resin adhesive has the characteristics of repeatable bonding and real-time change of fluorescence intensity with the bonding strength of the adhesive, so as to achieve visual tracking of the adhesive bonding process.

[0005] Another object of the present invention is to provide a method for preparing the aforementioned epoxy resin adhesive with visualized bonding process, which has the advantages of simple adhesive components, small amount of fluorescent agent added, simple synthesis process, easy industrialization, and wide application range. The fluorescent agent is introduced into the adhesive by dynamic covalent chemical cross-linking, which ensures the fluorescence intensity while not affecting the mechanical properties of the adhesive such as bonding strength.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical measures:

[0007] An epoxy resin adhesive with a visible bonding process, comprising component A and component B:

[0008] The component A is a furan-modified linear epoxy polymer (FEP) obtained by reacting a glycidyl ether monomer with 2-furanmethylamine, and its structural formula is as follows:

[0009] Where R1 is

[0010] The B component is a mixture of bismaleimide-modified tetraphenylethylene (TPE-2MI), bismaleimide and a compound (x-2MI), and its structural formula is as follows:

[0011]

[0012] Where R2 is

[0013] The preparation reaction formula of the TPE-2MI is as follows:

[0014]

[0015] In the present invention, TPE-2MI acts as both a fluorescent agent and a crosslinking agent, solving the problem of the precipitation of fluorescent dyes in traditional doped fluorescent adhesives, thereby affecting their fluorescence intensity and even the mechanical properties of the adhesives. TPE-2MI molecules can gradually release their fluorescent properties as the adhesive bonding process proceeds, meeting the requirements for visual tracking of the bonding process.

[0016] In order to further explain the reaction process of the above-mentioned whole process, the preparation method of the epoxy resin adhesive with visualization of the bonding process is as follows:

[0017] (1) mixing glycidyl ether monomer and 2-furylmethylamine in a molar ratio of epoxy group to amine group of 1-3:1, and stirring at 70° C. for 16 h to obtain FEP;

[0018] The molecular weight of the FEP is about 1000-2000 g / mol;

[0019] (2) After zinc powder, 4-aminobenzophenone and tetrahydrofuran are mixed, TiCl4 is added dropwise in an ice bath under anhydrous and oxygen-free conditions, followed by reflux for 12 hours, and the reaction is quenched with a 10% NaOH aqueous solution; after removing solid impurities by suction filtration, the organic phase is separated and dried with anhydrous MgSO4; the solvent is removed to obtain the product 4,4'-(1,2-diphenylethylene-1,2-diyl)diphenylamine (TPE-2NH2);

[0020] TPE-2NH2, maleic anhydride and tetrahydrofuran were mixed and stirred at room temperature for 12 hours. After the solvent was evaporated, a yellow solid was obtained, which was then directly dissolved in acetic anhydride. Anhydrous sodium acetate was then added and stirred at 75°C for 6 hours. After the solution was cooled to 0°C, a light yellow solid was precipitated. The precipitate was filtered and washed with hexane to obtain TPE-2MI.

[0021] (3) Component A, component B, and the solvent are uniformly mixed and then dried to obtain an epoxy resin adhesive with a visualized bonding process.

[0022] Among them, TPE-2MI is introduced into the adhesive by chemical cross-linking through DA reaction, and its fluorescence performance is affected by the cross-linking structure of the adhesive, thus establishing a synchronous change relationship between fluorescence and bonding strength. This solves the problem that the fluorescence intensity of current fluorescent adhesive products cannot be adjusted and the adhesion performance cannot be monitored in real time, and realizes real-time visual monitoring of the adhesive bonding strength through fluorescence intensity.

[0023] The adhesive needs to be cured at 80° C. for 1-5 hours.

[0024] The solvent is one of dichloromethane, chloroform, ethyl acetate and tetrahydrofuran.

[0025] The ratio of the total molar number of maleimide in the component B TPE-2MI and x-2MI to the molar number of furan groups of the epoxy polymer pendant group in the component A is 0.6-1.6.

[0026] The TPE-2MI content accounts for 0.5-20% of the component B by mole percentage.

[0027] The epoxy resin adhesive with visualized bonding process prepared by the present invention has the characteristics of repeatable bonding and real-time change of fluorescence intensity with the bonding strength of the adhesive. It can realize visualization of the adhesive bonding process and is expected to be applied to the fields of cultural relics restoration, medical treatment, automobile assembly, anti-counterfeiting, etc.

[0028] Compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:

[0029] A. The synthetic fluorescent adhesive of the present invention has simple components, a simple method and is easy to industrialize and produce.

[0030] B. The present invention introduces the fluorescent agent TPE-2MI into the adhesive, and utilizes the Diels-Alder (DA) reaction between the maleimide group and the furan group to cure the adhesive, thereby improving the bonding strength of the adhesive.

[0031] C. The DA reversible dynamic bond in the present invention provides the adhesive with cyclic bonding ability. After repeated bonding for 6 times, the bonding strength is still maintained at 79.9%.

[0032] D. The TPE-2MI molecules in the present invention act as fluorescent agents, and their fluorescence emission behavior is gradually released as the DA reaction proceeds during the bonding process, so that the fluorescence intensity of the adhesive gradually increases, which is conducive to visually monitoring the real-time bonding strength and bonding process of the adhesive using the fluorescence intensity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the FEP in Example 1 of the present invention 1 HNMR spectrum;

[0034] Figure 2 This is the GPC spectrum of FEP in Example 1 of the present invention;

[0035] Figure 3 is the TPE in Example 1 of the present invention 1 HNMR spectrum;

[0036] Figure 4 is the change trend of the fluorescence intensity, tensile shear strength and crosslinking density of the adhesive during the curing process in Example 1 of the present invention, wherein W is the tensile shear strength of the adhesive at different curing times, W0 is the tensile shear strength of the adhesive before curing, V e is the cross-linking density of the adhesive at different curing times, I is the fluorescence intensity of the adhesive at different curing times, and I0 is the fluorescence intensity of the adhesive before curing;

[0037] Figure 5 This is the cyclic bonding test of the adhesive in Example 1 of the present invention. Figure 5 (a) is the variation trend of tensile shear strength of adhesive in cyclic bonding test; Figure 5 (b) is the fluorescence intensity change trend of the adhesive in the cyclic bonding test, where I is the fluorescence intensity of the adhesive and I0 is the initial fluorescence intensity of the adhesive before curing. DETAILED DESCRIPTION

[0038] The present invention is described in detail below with reference to specific embodiments, but these embodiments should not limit the protection scope of the present invention in any way.

[0039] Example 1: An epoxy resin adhesive with a visualized bonding process, the preparation method thereof comprises the following steps:

[0040] A. Neopentyl glycol diglycidyl ether and 2-furylamine were mixed in a molar ratio of epoxy group to amine group of 1.5:1, and stirred at 70°C for 16 hours to obtain FEP.

[0041] B. The product was confirmed to be FEP by hydrogen nuclear magnetic resonance spectroscopy ( Figure 1 ), the structural formula is as follows, and its molecular weight is characterized by GPC ( Figure 2 ). The number average molecular weight of FEP is M n =774, weight average molecular weight M w =1193, FEP presents a monodisperse distribution, and the polymer dispersity index is 1.54.

[0042]

[0043] C. Zinc powder, 4-aminobenzophenone and tetrahydrofuran were mixed, TiCl4 was added dropwise in an ice bath and anhydrous and oxygen-free conditions, then refluxed for 12 hours, and the reaction was quenched with a 10% NaOH aqueous solution. After filtering to remove solid impurities, the organic phase was separated and dried with anhydrous MgSO4. The solvent was removed to obtain the product 4,4'-(1,2-diphenylethylene-1,2-diyl)diphenylamine (TPE-2NH2). TPE-2NH2, maleic anhydride and tetrahydrofuran were mixed and stirred at room temperature for 12 hours. After the solvent was evaporated, a yellow solid was obtained, which was then directly dissolved in acetic anhydride. Then anhydrous sodium acetate was added and stirred at 75°C for 6 hours. After the solution was cooled to 0°C, a light yellow solid precipitated. The precipitate was filtered and washed with hexane to obtain TPE-2MI.

[0044] D. The product was confirmed to be TPE by hydrogen nuclear magnetic resonance spectroscopy. Figure 3 ), the structural formula is as follows:

[0045]

[0046] E. Component B is a mixture of TPE-2MI and B-2MI, and the structural formula of B-2MI is as follows:

[0047]

[0048] F. Component A and component B are dissolved in dichloromethane to prepare a 40% solution, wherein the molar ratio of maleimide groups in component B to furan groups in component A is 1.3, and TPE-2MI accounts for 2% of the total molar number of component B. The organic solvent is evaporated at room temperature to obtain an epoxy resin adhesive with a visible bonding process.

[0049] Example 2: Characterization of the properties of the fluorescent adhesive prepared in Example 1.

[0050] A. Use the fluorescent adhesive in Example 1 to bond 304 stainless steel plates, cure at 80°C, and then cool to room temperature. By testing the fluorescence intensity, tensile shear strength, and crosslinking density of the adhesive with curing times of 0.3, 0.6, 1, 2, 3, 4, and 5 hours, it can be seen that when the curing time of the adhesive is within 3 hours, the fluorescence intensity, tensile shear strength, and crosslinking density of the adhesive will increase synchronously with the increase in curing time; when the curing time is greater than 3 hours, the adhesive is completely cured, and the fluorescence intensity, tensile shear strength, and crosslinking density of the adhesive no longer increase. The above data are as follows Figure 4 As shown. Figure 4 The blue line shows that the fluorescence intensity is linearly related to the tensile shear strength during the bonding process. 2 =0.995, indicating that the fluorescence performance of the adhesive during the bonding process has a reliable positive linear correlation with the bonding performance. In summary, the fluorescence intensity and bonding strength of the adhesive will increase with the increase of curing time, and the two are linearly correlated until the adhesive is completely cured, indicating that the bonding process of the adhesive can be monitored by fluorescence visualization. Among them, the tensile shear strength is tested according to the national standard GB / T 7124-2008.

[0051] B. Use the fluorescent adhesive in Example 1 to bond 304 stainless steel plates and cure them at 80°C for 3 hours to completely cure the adhesive. Heating the steel plates at 120°C for 10 minutes can de-crosslink the adhesive, and its fluorescence intensity will also decrease as the tensile shear strength decreases. The cyclic tensile test data of the adhesive is shown in Figure 5 As shown: Figure 5 (a) is the tensile shear strength of the adhesive during the cyclic bonding process. After 6 cross-linking-decross-linking cycles, the tensile shear strength is still 79.9% of the initial value; Figure 5 (b) is a graph showing the change in fluorescence intensity of the adhesive during the cyclic bonding process. The adhesive emits strong fluorescence after cross-linking and curing, while the fluorescence is greatly weakened after de-cross-linking, and the cyclic performance is good, that is, the fluorescence intensity of the adhesive changes synchronously with the bonding strength.

[0052] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be understood by anyone familiar with the technology within the technical scope disclosed by the present invention should be included in the scope of the present invention.

Claims

1. An epoxy resin adhesive with a visualized bonding process, characterized in that: It is composed of component A and component B: The component A is a furan-modified linear epoxy polymer obtained by reacting a glycidyl ether monomer with 2-furanmethylamine, denoted as FEP, and has the following structural formula: Where R1 is The B component is a mixture of bismaleimide-modified tetraphenylethylene and bismaleimide compounds, wherein the bismaleimide-modified tetraphenylethylene is denoted as TPE-2MI, and the bismaleimide compound is denoted as x-2MI, and the structural formula thereof is as follows: Where R2 is The ratio of the total molar number of maleimide in component B to the molar number of furan groups of the epoxy polymer pendant in component A is 1.3; The TPE-2MI content accounts for 2% of the component B by mole percentage.

2. A method for preparing an epoxy resin adhesive with visualized bonding process according to claim 1, characterized in that: The steps include: (1) mixing glycidyl ether monomer and 2-furylamine in a molar ratio of epoxy group to amine group of 1.5:1, and stirring at 70° C. for 16 h to obtain FEP; The number average molecular weight M of the FEP n =774, weight average molecular weight M w =1193, FEP presents monodisperse distribution, and the polymer dispersity index is 1.54; (2) After zinc powder, 4-aminobenzophenone and tetrahydrofuran were mixed, TiCl4 was added dropwise in an ice bath under anhydrous and oxygen-free conditions, followed by reflux for 12 h, and the reaction was quenched with a 10% NaOH aqueous solution; after filtering to remove solid impurities, the organic phase was separated and dried with anhydrous MgSO4; the solvent was removed to obtain the product 4,4'-(1,2-diphenylethylene-1,2-diyl)diphenylamine, recorded as TPE-2NH2; TPE-2NH2, maleic anhydride and tetrahydrofuran were mixed and stirred at room temperature for 12 hours. After the solvent was evaporated, a yellow solid was obtained, which was directly dissolved in acetic anhydride. Then, anhydrous sodium acetate was added and stirred at 75°C for 6 hours. After the solution was cooled to 0°C, a light yellow solid was precipitated. The precipitate was filtered and washed with hexane to obtain TPE-2MI. The preparation reaction formula of the TPE-2MI is as follows: (3) uniformly mixing component A, component B, and a solvent and then drying the mixture to obtain an epoxy resin adhesive with a visualized bonding process; The adhesive needs to be cured at 80°C for 1-5h; The solvent in step (3) is one of dichloromethane, chloroform, ethyl acetate and tetrahydrofuran.

Citation Information

Patent Citations

  • Tetraphenyl ethylene isomer having aggregation-induced emission and supramolecular polymerization properties and preparation method and application thereof

    CN109206374A